Perancangan dan Pembuatan Video Profil Sekolah SMKN 10 Batam sebagai Media Promosi Digital Menggunakan Metode MDLC - Muhammad Tsabit Tamani; Muhammad Dody Firmansyah; Syaeful Anas Aklani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2025)
This Research aims to design and produce a profile video for SMKN 10 Batam as a digital promotional medium. As a newly established school, SMKN 10 Batam requires visual media to introduce itself to the public. The video production process follows the Multimedia Development Life Cycle (MDLC) method, consisting of planning, design, material collection, assembly, testing, and distribution stages. Data were collected through observation, interviews, and visual documentation. The result is a 2–5 minute video showcasing the school's profile, which has been submitted to the school for promotional use. This activity benefits the school and provides practical experience for the student.